Coronary fistula resembling patent ductus arteriosus - Sgarbieri,Ricardo Nilsson (2003)
A 14-year-old girl, presenting with heart failure and a continuous murmur, similar to that of a patent arterial duct, was investigated using echocardiogram and cardiac catheterization revealing a left to right shunt throught a coronary artery fistulae between the first septal branch and the right ventricular outflow tract. The patient was submitted to surgery, occluding the anomalous branch by the suturing of its orifice in the right ventricular outflow tract, under cardiopulmonary bypass. After the operation, cardiac catheterization revealed complete occlusion of the fistula without any residual shunt or compromise to the coronary circulation. In seven years of follow-up the patient is completely free of symptoms.